Relationship between body mass index, liver enzymes and high-sensitivity C-reactive protein in type 2 diabetes mellitus patients - Kaur, Sukhmanjot; Sharma, Ritu; Kaur, Sukhraj (International Journal of Research in Medical Sciences, 2024)
Background: Obesity is a frequent co-morbid condition associated with excessive increase in weight. It is one of the most important modifiable risk factors in the pathogenesis of type 2 diabetes mellitus (T2DM). Obesity may be associated with liver disease and the progression of hepatic dysfunction. Also, highly sensitive C-reactive protein (hsCRP), which is elevated in inflammatory situations, can be produced by monocyte-derived macrophages in adipose tissue may also disrupt liver functions. Methods: A case control study with 50 patients of T2DM and 50 age and sex matched individuals were taken to serve as controls. Results: The body mass index (BMI) and waist circumference were increased in T2DM patients as compared to controls. However, the variations in liver enzymes alanine aminotransferase (ALT), aspartate aminotransferase (AST), and serum alkaline phosphatase (ALP) and hsCRP were increased in individuals of normal BMI as compared with individuals of overweight BMI. Conclusions: Individuals with normal Body mass index had an increased risk of developing T2DM along with progression of hepatic dysfunction. No associations were observed between chronic low-grade inflammation and BMI and with pathogenesis of obesity-related insulin resistance.